2004
DOI: 10.1152/japplphysiol.00923.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on the vascular reactivity of the whole kidney circulation in rabbits

Abstract: is known to improve vasodilating mechanisms mediated by endothelium-dependent relaxing factors in the cardiac and skeletal muscle vascular beds. However, the effects of exercise training on visceral vascular reactivity, including the renal circulation, are still unclear. We used the experimental model of the isolated perfused rabbit kidney, which involves both the renal macro-and microcirculation, to test the hypothesis that exercise training improves vasodilator mechanisms in the entire renal circulation. New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…Asghar et al (18) reported that TBARS depletion caused an increase in antioxidant defences and alleviated infl ammation in renal proximal tubules of trained rats. Although the exact mechanisms by which exercise counteracts L-NAME-induced renal injuries are unclear, they may involve increased NO bioavailability and enhanced responsiveness of the renal vascular smooth muscle to NO (28). In fact, under aerobic conditions, NO can inhibit TBARS formation by decomposing primary lipid peroxidation products (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Asghar et al (18) reported that TBARS depletion caused an increase in antioxidant defences and alleviated infl ammation in renal proximal tubules of trained rats. Although the exact mechanisms by which exercise counteracts L-NAME-induced renal injuries are unclear, they may involve increased NO bioavailability and enhanced responsiveness of the renal vascular smooth muscle to NO (28). In fact, under aerobic conditions, NO can inhibit TBARS formation by decomposing primary lipid peroxidation products (29).…”
Section: Discussionmentioning
confidence: 99%
“…De Moraes et al (28) proposed that increases in cardiac output during exercise, associated with renal vasoconstriction and upregulation of endothelial NOS, could enhance blood fl ow velocity and shear stress in kidney circulation. In addition, they have shown that renal hyperaemia occurring immediately after exercise inactivates vascular ROS and consequently prevents ROS interaction with NO by upregulating free-radical scavenger systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging alters both the endothelium and the VSMC [34], and endothelium-independent response can be altered in presence of hyperinsulinemia in patients with metabolic syndrome [64] or by acute hyperhomocysteinemia in diabetic patients [12]. On the other hand, EX has been shown to increase the relaxant response to NO donors in humans and rabbits [15,33], demonstrating that it can reverse and/or counteract the dysfunctional VSMC relaxant capacities. The mechanism involved in the impaired SNP response remains elusive; nonetheless, the equally reduced endothelium-dependent relaxation to Ach was prevented in the presence of indomethacin.…”
Section: Endothelium-independent Functionsmentioning
confidence: 99%
“…Endurance training of healthy sedentary human subjects results in increased cardiac output and stroke volume (1). Chronic exercise is also known to improve the vasodilatory mechanisms mediated by endothelium-dependent relaxing factors in the cardiac and skeletal muscles, as well as kidney, cutaneous and other vascular beds (2)(3)(4). Decreased blood pressure induced by exercise training was also reported in hypertensive subjects and spontaneously hypertensive rats (5,6).…”
Section: Introductionmentioning
confidence: 99%